Multiple thoracotomy for metastatic pulmonary neoplasm. Issue 2 (March 1974) - Marks, Peter
Abstract : Marks, P. (1974). Thorax, 29, 248-251. Multiple thoracotomy for metastatic pulmonary neoplasm. Surgical excision of solitary, metastatic, malignant lesions of the lung is reported as of benefit in certain cases in which the primary tumour apparently has been completely removed and in which there is no evidence of further metastatic spread. It has been shown that in a few instances survival for many years may be expected to follow such a procedure, while at other times the degree of palliation of pulmonary symptoms makes the operation worthwhile. Two patients who had metastatic lung deposits successfully removed are described. Further pulmonary metastases, without evidence of metastases elsewhere or recurrence of the original lesion, were resected. In both cases remarkable palliation of symptoms was afforded and both are alive at the time of writing (1 November 1973).